THE EFFECT OF PLYOMETRICS TRAINING ON EXPLOSIVE POWER OF MEDICAL STUDENTS IN DIPONEGORO UNIVERSITY - Pramatama Andhika Sunarso Pandoyo; Darmawati Ayu Indraswari; Marijo Marijo; Yuriz Bakhtiar (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Introduction : Explosive power are the combination maximum strength and maximum velocity. High value of muscle strength and velocity can lead to good measurement of explosive power. Plyometrics training known as an exercise that can increased explosive power. This exercise is really popular among athletes and has proven to increase their explosive power. However, there’s still no further study that measured explosive power on medical students after given plyometrics training treatment. Methods : Quasi experimental study of plyometrics training has done for 6 weeks to medical students Diponegoro University. 28 subjects was divide into 2 groups : plyometrics training (as treatment group) and control group (as non-treatment group). Vertical jump test score was measurement in pre-test, middle-test, and post-test. The explosive power measured by vertical jump test. The results were analyzed by SPSS software. Results : The explosive power improved among subjects in plyometrics treatment group. During the plyometrics treatment, vertical jump was singnificantly increase during treatment in pre-test to mid-test (35.93 cm to 49,21 cm ; P : <0.001) and mid-test to post-test measurement (49.21 cm to 54.21 cm ; P : <0.001). Vertical jump score significantly increase in plyometrics group compare to control group ; on middle-test (<0.001 vs 0.344 ; P 0.019) and post-test (<0.001 vs 729 ; P 0.001) measurement respectively. Conclusions : Plyometrics training improved lower limb explosive power in male medical students of Diponegoro University. This is marked by significantly increase among subjects in plyometrics treatment group.Keywords: Plyometrics Training, Explosive Power, Vertical Jump Test